Defining a Unified Model of Vocabulary Acquisition via Extensive Reading : Final Report. - Uitdenbogerd, Alexandra Louise; Kablaoui, Sara; Martin, Aidan (Office for Learning and Teaching, 2017)
Post-secondary students with English as a second language (L2) often struggle with reading their textbooks, and other language-related tasks associated with their coursework, despite achieving the minimum IELTS entry requirement. Much of the difficulty is due to the large difference in the known English vocabulary range of L2 speakers compared to native speakers. Extensive reading, or reading for pleasure, is one method of naturally acquiring vocabulary. However, while past studies into vocabulary acquisition agree that vocabulary is acquired, they disagree greatly about the rate of acquisition with some saying the rate is too low to be useful, especially for academic environments. Many conclusions of these studies were inconsistent due to not applying knowledge of the statistical properties of text. This is the final report from a project that tested a model based on a meta-study of past research with learners of English so that extensive reading can be appropriately used in future language learning courses.